Analysis of the epidemiological status, microbiology, treatment methods and financial burden of hematogenous osteomyelitis based on 259 patients in Northwest China - Lu, Shuaikun; Wang, Linhu; Luo, Wen; Wang, Guoliang; Zhu, Zhenfeng; Liu, Yunyan; Gao, Hao; Fu, Congxiao; Ren, Jun; Zhang, Yunfei; Zhang, Yong (Frontiers in Endocrinology, 2023)
Background: The incidence of hematogenous osteomyelitis is on the rise, and the prognosis is poor. There has been no large-scale epidemiological analysis of hematogenous osteomyelitis in the world, and the treatment method is still controversial. The aim of this study was to investigate the epidemiological status, microbiological characteristics, treatment and financial burden of hematogenous osteomyelitis in Northwest China to explore the therapeutic effects of different treatment methods, elucidate the epidemiological characteristics of hematogenous osteomyelitis and to provide a basis for the choice of treatment. Methods: A retrospective case study method was used to collect and analyze clinical data obtained from patients with hematogenous osteomyelitis in a tertiary hospital in Northwest China from January 1, 2011, to December 31, 2020. Results: We included 259 patients with hematogenous osteomyelitis, including 96 patients with acute hematogenous osteomyelitis and 163 patients with chronic hematogenous osteomyelitis. The cause of the disease was not obvious in most patients, the sex ratio of males to females was 1.98, and the three most common infected sites were the tibia, femur and phalanx. Regarding preoperative serum inflammatory markers, the rate of positivity for ESR was the highest at 67.58%. Among pathogenic microorganisms, Staphylococcus aureus was the most common. Regarding the financial burden, the median total cost per patient was 25,754 RMB, and medications accounted for the largest proportion of the main costs. Conclusions: The most common pathogen associated with HO infection was MSSA. Oxacillin has good PK and PD and is recommended as the first-line drug. Some blood-borne bone infections may lead to complications, such as pulmonary infection through bacteremia, which requires early detection to avoid a missed diagnosis. Regarding surgical intervention, debridement plus absorbable calcium sulfate bone cement and calcium sulfate calcium phosphate bone cement exclusion have achieved good therapeutic effects, but they are worthy of further in-depth research. Regarding the financial burden, the median total cost per patient was 25,754 RMB. The financial burden of blood-borne osteomyelitis was lower than that of traumatic osteomyelitis. Among the main costs, drugs accounted for the largest proportion.